Time-course effects of cognitively engaging physical activity on executive function and self-control in younger school-aged children: a randomized controlled trial - Xu, Yifan; Qi, Kai; Białas, Marcin; Xu, Qi; Guo, Xiaodan; Chen, Aiguo (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the time-course effects of cognitively engaging physical activity (CEPA) on executive function (EF) and self-control in younger school-aged children (ages 8–10 years) exploring the differential impacts and temporal dynamics of the intervention.MethodsUsing a cluster randomized controlled trial design, 203 younger school-aged children (age = 8.9 ± 0.67, male 54.7%, female 45.3%) were randomly allocated into either an experimental group receiving CEPA or a control group receiving the traditional physical education curriculum. The intervention lasted 10 weeks, occurring three times per week, 45 min per session, structured according to a “graded cognitive load” principle, progressively increasing cognitive complexity and challenges. Assessments of EF (inhibitory control, working memory, cognitive flexibility) and self-control (social interaction, emotional experience, learning behaviors, daily habits) were conducted at baseline, immediately post-intervention, and at a three-month follow-up. Linear mixed-effects models were used to account for the clustered study design.ResultsLinear mixed-effects models revealed significant time-by-group interaction effects for executive function components: inhibitory control (p = 0.020, ICC = 0.057) and working memory (p = 0.002, ICC = 0.054), with cognitive flexibility showing a trend toward significance (p = 0.077, ICC = 0.000). A significant interaction effect was also observed for the total self-control score (p < 0.001, ICC = 0.040). The experimental group demonstrated significant improvements in executive function, with working memory showing substantial immediate gains, and inhibitory control exhibiting strong retention. Regarding self-control dimensions, the most pronounced improvements occurred in social interaction (p < 0.001, ICC = 0.000) and learning behavior (p < 0.001, ICC = 0.072). Overall, intervention effects displayed a nonlinear time-course, characterized by rapid improvements during the intervention phase, slight attenuation at follow-up but remaining significantly above baseline levels, whereas no significant changes were observed in the Traditional Physical Education Curriculum control group.ConclusionThis study systematically confirms the immediate and lasting effectiveness of CEPA on younger school-aged children’s executive function and self-control, highlighting the differential effects across cognitive and behavioral domains and their nonlinear temporal characteristics. These findings underscore the value of integrating cognitive engagement elements into the school-based physical education curriculum, offering robust empirical support for educational practices and policy decisions aimed at comprehensive cognitive and behavioral development among children.